Medical education abroad: experience and perceived learning effects of German medical students in an international cardiology elective - Albert, Christian; Werwick, Katrin; Gottschalk, Marc; Aschoff, Anna; Auricchio, Angelo; Braun-Dullaeus, Rüdiger C.; Stieger, Philipp (Frontiers in Medicine, 2025)
BackgroundWith the aim of increasing study abroad courses the University Clinic for Cardiology and Angiology at the Otto-von-Guericke University Magdeburg (Magdeburg, Germany) in collaboration with the Istituto Cardiocentro Ticino (Lugano, Switzerland), established an intensive time-delimited student course to provide cardiological teaching content and insight beyond the regular curriculum. An underlying blueprint with learning objectives was formulated in order to ensure the training outcome. Within the present study, students’ individual perceptions of training in Italian-speaking Switzerland are assessed.MethodsThree focus groups discussions with elective graduates were performed (N = 18 course participants). Discussions were recorded, transcribed, and anonymized.We performed a qualitative content analysis in accordance with Mayring and thereby formed an inductive category system. Categorized themes were analyzed to describe students’ perceptions and evaluations of the elective subjects.ResultsIn total N = 17/18 (94.4%) of the elective students participated in the group discussions. In general, teaching practical clinical and patient centered issues with high degree of interaction between the students and lecturers were acknowledged by the students.In the Lugano elective, differences in the organization of the different healthcare systems and hospitals were noted. To experience medicine not only in a foreign context but also with different languages (English/Italian) was challenging but without particular problems.Interdisciplinary and interprofessional aspects were less experienced. Ultimately, students showed a high level of reflection regarding their learning and teaching experience and gained more motivation to continue studying cardiology and a strong tendency to consider cardiology as a future specialist discipline.ConclusionDuring the course of medical education, intensive courses and teachers’ engagement in particular topics can increase a student’s enthusiasm for the discipline. Similarly, temporary international experiences may foster interest in a selected area or discipline. Efforts to increase the possibilities in the medical school curriculum for studies abroad might positively influence the educational experience. Consideration may be given to implement such offerings at an earlier juncture to support interested students.